Mastering Core Recommendations during HEPAtology ROUNDS in Patients with Advanced Chronic Liver Disease - Garcia-Saenz-de-Sicilia, Mauricio; Al-Obaid, Lolwa; Hughes, Dempsey L.; Duarte-Rojo, Andrés (Seminars in Liver Disease, 2022)
Efficient and thorough care of hospitalized patients with advanced chronic liver disease is of utter importance to improve outcomes and optimize quality of life. This requires understanding current evidence and best practices. To facilitate focus on up-to-date knowledge and a practical approach, we have created the HEPA-ROUNDS mnemonic while outlining a practical review of the literature with critical appraisal for the busy clinician. The HEPA-ROUNDS mnemonic provides a structured approach that incorporates critical concepts in terms of prevention, management, and prognostication of the most common complications frequently encountered in patients with advanced chronic liver disease. In addition, implementing the HEPA-ROUNDS mnemonic can facilitate education for trainees and staff caring for patients with advanced chronic liver disease.
Keywords: Advanced Chronic Liver Disease; cirrhosis; hepatorenal syndrome; hyponatremia; albumin; prophylaxis